2007
DOI: 10.2977/prims/1201012035
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Pseudodifferential Operators

Abstract: In previous papers, a generalization of the Weyl calculus was introduced in connection with the quantization of a particle moving in R n under the influence of a variable magnetic field B. It incorporates phase factors defined by B and reproduces the usual Weyl calculus for B = 0. In the present article we develop the classical pseudodifferential theory of this formalism for the standard symbol classes S m ρ,δ . Among others, we obtain properties and asymptotic developments for the magnetic symbol multiplicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
230
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(234 citation statements)
references
References 41 publications
1
230
0
3
Order By: Relevance
“…These phases appear very naturally in the continuous case, see [7,8,19,22,23,24,25,26], where it is shown that if a(x) is the transverse gauge generated by a globally bounded magnetic field |b(x)| ≤ 1, then φ(x, x ′ ) can be chosen to be the path integral of a(x) on the segment linking x ′ with x. This is the same as the magnetic flux of b through the triangle generated by x, x ′ and the origin.…”
Section: Previous Results and Open Problemsmentioning
confidence: 99%
“…These phases appear very naturally in the continuous case, see [7,8,19,22,23,24,25,26], where it is shown that if a(x) is the transverse gauge generated by a globally bounded magnetic field |b(x)| ≤ 1, then φ(x, x ′ ) can be chosen to be the path integral of a(x) on the segment linking x ′ with x. This is the same as the magnetic flux of b through the triangle generated by x, x ′ and the origin.…”
Section: Previous Results and Open Problemsmentioning
confidence: 99%
“…The gauge-covariance of the modified H (2) A in contrast to H (1) A in Ichinose-Tamura [13] was emphasized in Iftimie-Mȃntoiu-Purice [14,15,16] . Let us observe some of these facts in the following.…”
Section: However H (2)mentioning
confidence: 99%
“…A + V is defined with term H (2) A being the pseudo-differential operator modified by Iftimie-Mȃntoiu-Purice [13,14,15]:…”
Section: Definition 21 the First H (1) := H (1)mentioning
confidence: 99%
“…The magnetic Weyl calculus [IMP07,KO02,MP04,MP10,MPR07] has as a background the problem of quantization of a physical system consisting in a spinless particle moving in the euclidean space X ∼ = R n under the influence of a magnetic field, i.e. a closed 2-form B on X (dB = 0), given in a base by matrix-component functions B jk = −B kj : X → R, j, k = 1, .…”
Section: Some Examplesmentioning
confidence: 99%
“…The present paper is devoted to developing a set of techniques applicable to operator valued maps on measure spaces π : (Σ, µ) → B(H) that satisfy a square integrability property analogous to that of locally compact group representations (see (2.4) below) although π may not be a group representation and µ may not be a Haar measure. This investigation was motivated by several situations when actually Σ is a group that fails to be locally compact so it does not admit any Haar measure (as for instance in the study of the canonical commutation relations where one has been looking for suitable substitutes of the group algebra for inductive limit groups [Gru97,GN09,GN13]), or when Σ is locally compact but π is not even a projective group representation (see for instance the orthogonality relations for irreducible representations of nilpotent Lie groups: [HM79,Pe94,Wo13], and the references therein; or the magnetic Weyl calculus [MP04,IMP07,MP12,BB09,BB11a]). …”
Section: Introductionmentioning
confidence: 99%